2014
DOI: 10.1158/0008-5472.can-14-1161
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence of a Precisely Tuned Dysregulation in the Hypoxia Signaling Pathway during Oncogenesis

Abstract: The classic model of tumor suppression implies that malignant transformation requires full 'two-hit' inactivation of a tumor suppressor gene. However, more recent work in mice has led to the proposal of a "continuum" model that involves more fluid concepts such as gene dosage-sensitivity and tissue specificity. Mutations in the tumor suppressor gene VHL are associated with a complex spectrum of conditions. Homozygotes or compound heterozygotes for the R200W germline mutation in VHL have Chuvash polycythemia, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…This observation confirms the hypothesis of a continuum model of tumor suppression by VHL. 21,31 Regarding the erythrocytosis developed in patients homozygous for D143D, both probands (F9 II.1 and F10 II.1) presented mutations in the b-globin gene (HBB) that induced hemoglobin instability or thalassemia (Table 1). This may have compensated for the strong erythropoiesis associated with a very high serum erythropoietin level associated with the D143D mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation confirms the hypothesis of a continuum model of tumor suppression by VHL. 21,31 Regarding the erythrocytosis developed in patients homozygous for D143D, both probands (F9 II.1 and F10 II.1) presented mutations in the b-globin gene (HBB) that induced hemoglobin instability or thalassemia (Table 1). This may have compensated for the strong erythropoiesis associated with a very high serum erythropoietin level associated with the D143D mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Exons and exon-intron junctions of the VHL gene were sequenced from DNA extracted from whole blood, as previously described. 21…”
Section: Sanger Sequencingmentioning
confidence: 99%
“…Couvé et al found ZNF395 among the genes whose expression was increased in the ccRCC of patients bearing two gene mutations in the tumor suppressor gene von Hippel-Lindau VHL . The upregulation of a cluster of 17 genes including ZNF395 is correlated with the risk of the development of ccRCC implying a functional relevance of ZNF395 in disease progression [ 16 ]. A hypoxic induction of ZNF395 was also detected in mature SGBS (Simpson-Golabi-Behmel syndrome) adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF395 was also described as a hypoxia-inducible gene in various glioblastoma, as well as other tumor cell lines [ 8 , 9 ], and was found to be activated by cyclic and chronic hypoxia [ 10 ]. Increased expression of ZNF395 could be associated with a poor prognosis in patients with osteosarcomas, Ewing sarcomas [ 11 , 12 ], and neuroblastomas [ 13 ] and may also play a role in the pathogenesis of clear cell renal cell carcinoma (ccRCC) [ 14 16 ]. These observations support a functional role of ZNF395 in the response of tumor cells to hypoxia and in the pathogenesis of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In a hypoxic region, an anaerobically metabolising cell is expected to have a fitness advantage over an aerobically metabolising cell and so should repopulate the hypoxic region, but the opposite should be true in a normoxic region 63 . Such different phenotypes may be genetically determined (such as the case of VHL/HIF1 mutants in kidney cancer) 64 , or they may be a consequence of plasticity in cellular behaviours 15 , and furthermore there may be feedback between the tumour cells and their microenvironment that drives specialisation of tumour cells and the concomitant strengthening of microenvironmental gradients.…”
Section: The Origins Of Intra-tumour Heterogeneitymentioning
confidence: 99%